2017
DOI: 10.3892/br.2017.914
|View full text |Cite
|
Sign up to set email alerts
|

The level of serum carcinoembryonic antigen is a surrogate marker for the efficacy of EGFR-TKIs but is not an indication of acquired resistance to EGFR-TKIs in NSCLC patients with EGFR mutationsm

Abstract: Abstract. The aim of the present study was to define the relationship between carcinoembryonic antigen (CEA) and survival in non-small cell lung cancer (NSCLC) patients receiving epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) and to investigate whether the level of serum CEA is related to the mechanism for acquisition of resistance to EGFR-TKIs. A total of 100 patients with advanced NSCLC (stage IIIB or stage IV) and harboring EGFR mutations were included. All patients received erlotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The expected survival benefit of EGFR-TKI treatment was higher in MPE patients with elevated PF-CEA levels. This observation is consistent with those in previous studies that demonstrated the greater efficacy of EGFR-TKI treatment in patients with elevated S-CEA levels [ 19 , 20 ]. One hypothesis states that a possible antiapoptotic signal of the mutant EGFR pathway may enhance CEA protein expression in tumors [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The expected survival benefit of EGFR-TKI treatment was higher in MPE patients with elevated PF-CEA levels. This observation is consistent with those in previous studies that demonstrated the greater efficacy of EGFR-TKI treatment in patients with elevated S-CEA levels [ 19 , 20 ]. One hypothesis states that a possible antiapoptotic signal of the mutant EGFR pathway may enhance CEA protein expression in tumors [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported the relationship between tumour markers and the effect of NSCLC therapy, including EGFR-TKIs. CEA level has been demonstrated to be associated with the prognosis of patients on EGFR-TKIs and other treatments for NSCLC 7,25,26. In our study, a higher CEA level was associated with a poor outcome of EGFR-TKI (9.6 mo.…”
Section: Discussionsupporting
confidence: 53%
“…Especially CYFRA 21-1 demonstrated high prognostic relevance across various therapeutic settings, stages and histologic subgroups. While elevated STM levels were often associated with poor prognosis, the relationship with CEA in TKI therapies was more controversial, as high CEA levels also predicted longer OS [113] and PFS in several studies [99][100][101][102][103][104]. A growing number of studies considered the inclusion of established clinical prognostic markers such as performance score, TNM stage, and histology, which were also the most important clinical parameters with prognostic relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, it was found that low CEA levels had a negative predictive value for PFS in patients treated with TKIs [99][100][101][102][103][104], but also in those undergoing chemotherapy and/or radiotherapy [33] and immunotherapy [43], reflecting the low comparability of individual studies with different conclusions drawn. A randomized phase II trial [99], investigating 138 advanced NSCLC patients treated either with combinations of the VEGFR/PDGFR inhibitor linifanib and chemotherapy or chemotherapy alone reported longer PFS in patients with high CEA >3 ng/mL and low CYFRA 21-1 <7 ng/mL signature in the TKI arm.…”
Section: Other Serum Tumor Markers and Combinationsmentioning
confidence: 99%